Performance comparison between isothermal hot corrosion and in situ cyclic hot corrosion of nickel-based superalloys - Syed, Adnan U.; Martinez, Fabian Duarte; Roberts, Tracey; Encinas-Oropesa, Adriana; Morar, Nicolau I.; Grohne, Marlene; Frommherz, Martin; Nicholls, John R.; Gray, Simon (Springer, 2021)
Although a lot of work has been done to understand both major mechanisms of hot corrosion, namely type I (high-temperature hot corrosion) and type II (low temperature hot corrosion), there is very little information available on more representative cyclic performance in these regimes. This work addresses this by assessing the performance of isothermal (type I and type II) hot corrosion tests against combined (short and long) cyclic corrosion tests. Single-crystal alloy PWA 1484 and directionally solidified alloy MAR-M247 were assessed in all test regimes. Pre- and post-exposure dimensional metrology was used to quantify the corrosion damage and characterised using SEM/EDX. This paper highlights that the results of short cycle test conditions are more damaging compared to long cycle and standard isothermal type I and II test conditions. The cast nickel-based alloy MAR-M247 was found to be a better performer compared to PWA 1484 single-crystal alloy.
Keywords: PWA 1484; MAR-M247; Thermal cyclic; Isothermal; Hot corrosion